Fielding baseball skills and drills (ABCA's Baseball Skills and Drills video series, 2001)
Fielding is one of three tapes in the ABCA's Baseball Skills & Drills video series. Hitting and Baserunning and Pitching and Catching as well as a comprehensive companion book titled Baseball Skills & Drills provide a superb set of instructional tools for players and coaches.